Coach procesu głównego jako antidotum na rozciąganie łańcuchów wartości procesów cząstkowych - Perechuda, Kazimierz (Coach of the basic process as the antidotum to small added value of the part processes, 2006)
In the paper are presented: the dilemma of the continuity and discontinuity in the process management, the value of the synthesis of the processes, the life cycle of the processes, the function, role and tasks of the coach of the basic process.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1134, s. 41-46